All Days 2000
DOI: 10.2118/65157-ms
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Geomechanics and Geophysics for Reservoir Seismic Monitoring Feasibility Studies

Abstract: Seismic measurements acquired at different stages in the life of a reservoir can monitor the fluid distribution over production time. Changes in saturation, pore pressure and stresses, induced by reservoir production may influence the process of wave propagation in rocks. The variations in mean effective stresses, due to changes in mean stress or /and pore pressure, are not always integrated in a proper manner. We present here a methodology to evaluate what is the contribution of a geomechanical approach on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The resulting reservoir model constitutes the best possible input to determine whether subsequent 4D monitoring is feasible or not (Khan et al, 2000;Vidal et al, 2000). It is usually conducted for the given reservoir using measured rock, fluid properties, and reservoir simulation model.…”
Section: Feasibility Study Of 4d Projectmentioning
confidence: 99%
“…The resulting reservoir model constitutes the best possible input to determine whether subsequent 4D monitoring is feasible or not (Khan et al, 2000;Vidal et al, 2000). It is usually conducted for the given reservoir using measured rock, fluid properties, and reservoir simulation model.…”
Section: Feasibility Study Of 4d Projectmentioning
confidence: 99%
“…In the original Hertz-Mindlin theory n is identical to 3. Some laboratory measurements of samples proposed a larger number for n. Vidal [11] discovered n = 5.6 for Pwaves and n = 3.8 for shear waves for gas sands, while Landrø [12] employed n = 5 for oil sands. We use n = 5 in this study.…”
Section: Rock Physic Modelsmentioning
confidence: 99%
“…Vidal et al 30 found n=5.6 for the P-wave and n=3.8 for the S-wave in gas sands, while Landrø 31 used n=5 for oil sands. This correction is used for developing forward modeling in this study (n=5 instead n=3).…”
Section: Appendix a Gassmann Equationmentioning
confidence: 99%